Effect of growth regulators concentrations on in vitro multiplication of three elite sugarcane (Saccharum officinarum L.) Genotypes using shoot tip culture - Amente, Gerema; Feyissa, Tileye (Journal of Scientific Agriculture, 2022)
Conventional vegetative propagation of sugarcane generally has low multiplication rate and allows distribution of diseases. Micropropagation is the only practical means of achieving rapid, large-scale production of disease-free quality planting material. Experiments on shoot tip culture initiation and shoot multiplication were laid out in completely randomized design with 2x3x3 and 4x5x3 factorial treatment arrangements respectively. Data were subjected to analysis of variance (ANOVA) and significant means were separated using Duncan’s multiple range tests. With regard to shoot multiplication, genotype Q200 showed a maximum of 13.59 shoots per explant with 5.83cm shoot length on a medium fortified with 2 mg/l BAP alone, while genotype Q217 produced a maximum of 15.28 shoots per explant with 5.37cm mean shoot length on a medium supplied with 2.0 mg/l BAP and 0.25 mg/l kinetin. Likewise, Co-0238 produced a maximum of 13.56 shoots per explant with a mean shoot length 6.50 cm on medium fortified with 1.5 mg/l BAP + 0.5mg/l kinetin.